Prentice Hall science explorer : (Pearson Prentice-Hall, 2005)
Prentice Hall Science Explorer-Astronomy. School textbook. Chapters include:Exploring Space, The Solar System, Earth, Moon and Sun, and Stars, Galaxies, and the Universe. 2009 Edition, Hardcover